Controlling molecular dynamics by exciting atoms in a cavity - Csehi, András; Szabó, Krisztián; Vibók, Ágnes; Cederbaum, Lorenz S.; Halász, Gábor J. (Physical review letters, 2025)
Placing an atom and a molecule in a cavity opens the door to initialize molecular dynamics by exciting a level of the atom. This approach enlarges the range of choosing the light source to trigger molecular dynamics substantially. The interplay of the atomic, molecular, and photonic populations gives rise to rich dynamics. The cavity photon plays the role of a mediator between the atom and the molecule and it is found that the photonic population is rather low throughout and its evolution follows that of the molecule. Cavities are known to be subject to losses. In spite of the losses it is demonstrated that the presence of the atom gives rise to a long-lived dynamics that should be of relevance for experimental investigations. The presence of more atoms and molecules is expected to further enrich the dynamics.
Veröffentlicht: 5. Mai 2025
Gesehen am 17.10.2025